(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2019)
This essay introduces a realistic look at our laws of gravity, and the effects thereof, and it goes beyond to reveal how and by what gravity comes about in the fundamentals of nature upon which the earth and all spheres rest.